Bank Responsibility and Supply Chain Management in Banking System Effects Due to Debt Collectors Intimidation to its Customers - Agus Budiman; Etty Mulyati; Supraba Sekarwati Widjayani; Tarsisius Murwadji (International Journal of Supply Chain Management, 2019)
Abstract- This study aims to determine the extent to which the Banking or Financial Institutions oversee and are responsible for the third party (debt collector) in collecting debts to debtors or customers because of bad credit. The study used qualitative descriptive research, The research by analyzing and providing an of what really happened and collecting data obtained directly from the victims of field officers (debt collector). Also, the supply chain management effects are investigated in banking system efficiency. The data were taken by interviewing, observation, and documentation. From this research, the results of the lack of supervision and responsibility of the Banking or Financial Institutions on what is done by the debt collector to the bank customer or banking service consumers and/or financial institutions, And how the legal sanctions should have a deterrent effect and do not cause turmoil in the social life of the community, which upholds the dignity of a dignified society.